2019
DOI: 10.5230/jgc.2019.19.e42
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Linear-Shaped Gastroduodenostomy during the Performance of Totally Robotic Distal Gastrectomy

Abstract: Purpose: Although linear-shaped gastroduodenostomy (LSGD) was reported to be a feasible and reliable method of Billroth I anastomosis in patients undergoing totally laparoscopic distal gastrectomy (TLDG), the feasibility of LSGD for patients undergoing totally robotic distal gastrectomy (TRDG) has not been determined. This study compared the feasibility of LSGD in patients undergoing TRDG and TLDG. Materials and Methods: All c: onsecutive patients who underwent LSGD after distal gastrectomy for gastric cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For RDG, Lu’s RCT study showed that patients in the RDG group reduced postoperative morbidity compared with LDG group (9.2% vs 17.6%, p=0.039). 12 As the incidence rates in the TRDG group range from 4.7% to 15.9% in retrospective studies 16 31 32 and given the proficiency of surgeons who perform robotic gastrectomy and the reasonable cost-effectiveness of robotic surgery, 9.0% is the expected 30-day postoperative morbidity in the TRDG group in this study. PASS V.15.0 software was used to calculate sample sizes of 307 with a 1:1 ratio in each group, achieving 80% power to detect a difference between the group proportions of 7.5%.…”
Section: Methods and Analysismentioning
confidence: 76%
See 1 more Smart Citation
“…For RDG, Lu’s RCT study showed that patients in the RDG group reduced postoperative morbidity compared with LDG group (9.2% vs 17.6%, p=0.039). 12 As the incidence rates in the TRDG group range from 4.7% to 15.9% in retrospective studies 16 31 32 and given the proficiency of surgeons who perform robotic gastrectomy and the reasonable cost-effectiveness of robotic surgery, 9.0% is the expected 30-day postoperative morbidity in the TRDG group in this study. PASS V.15.0 software was used to calculate sample sizes of 307 with a 1:1 ratio in each group, achieving 80% power to detect a difference between the group proportions of 7.5%.…”
Section: Methods and Analysismentioning
confidence: 76%
“…At present, the safety and feasibility of TLDG and TRDG has been proven. 16 However, no prospective study has compared short-term outcomes and quality of life (QOL) for TLDG and TRDG with intracorporeal anastomosis for clinical stage I–III patients to our knowledge. To evaluate how different surgical approaches affect short-term outcomes and QOL for patients with gastric cancer, it is necessary to carry out this multi-institutional randomised controlled trial.…”
Section: Introductionmentioning
confidence: 99%